2016
DOI: 10.1071/fp15312
|View full text |Cite
|
Sign up to set email alerts
|

Rutin, a flavonoid with antioxidant activity, improves plant salinity tolerance by regulating K+ retention and Na+ exclusion from leaf mesophyll in quinoa and broad beans

Abstract: The causal relationship between salinity and oxidative stress tolerance is well established, but specific downstream targets and the role of specific antioxidant compounds in controlling cellular ionic homeostasis remains elusive. In this work, we have compared antioxidant profiles of leaves of two quinoa genotypes contrasting in their salt tolerance, with the aim of understanding the role of enzymatic and non-enzymatic antioxidants in salinity stress tolerance. Only changes in superoxide dismutase activity we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(59 citation statements)
references
References 59 publications
5
54
0
Order By: Relevance
“…NaCl sequestration capacity may be the most critical function of salt bladders in young leaves of Aizoaceae and Amaranthaceae halophytes (Agarie et al, 2007; Bonales-Alatorre et al, 2013; Barkla et al, 2016), but as the leaf matures and the salt bladders reach their maximum volume, salt sequestration rate needs to be paused (Adams et al, 1998; Jou et al, 2007; Barkla and Vera-Estrella, 2015; Oh et al, 2015). Other functions including providing a secondary epidermal layer to protect against water loss, UV stress, and also serving as reserves for ROS scavenging metabolites and organic osmoprotectants may contribute more to plant survival under abiotic stress as the leaf matures (Adolf et al, 2013; Barkla and Vera-Estrella, 2015; Ismail et al, 2015; Oh et al, 2015). The corresponding increased rate of salt secretion as a response to increasing concentrations of soil NaCl is also observed for salt glands in other plant clades (Marcum et al, 1998; Mishra and Das, 2003).…”
Section: Salt Glands Have Evolved Independently Many Timesmentioning
confidence: 99%
“…NaCl sequestration capacity may be the most critical function of salt bladders in young leaves of Aizoaceae and Amaranthaceae halophytes (Agarie et al, 2007; Bonales-Alatorre et al, 2013; Barkla et al, 2016), but as the leaf matures and the salt bladders reach their maximum volume, salt sequestration rate needs to be paused (Adams et al, 1998; Jou et al, 2007; Barkla and Vera-Estrella, 2015; Oh et al, 2015). Other functions including providing a secondary epidermal layer to protect against water loss, UV stress, and also serving as reserves for ROS scavenging metabolites and organic osmoprotectants may contribute more to plant survival under abiotic stress as the leaf matures (Adolf et al, 2013; Barkla and Vera-Estrella, 2015; Ismail et al, 2015; Oh et al, 2015). The corresponding increased rate of salt secretion as a response to increasing concentrations of soil NaCl is also observed for salt glands in other plant clades (Marcum et al, 1998; Mishra and Das, 2003).…”
Section: Salt Glands Have Evolved Independently Many Timesmentioning
confidence: 99%
“…Osmotic adjustment for survival of plants under high salinity is linked to K + retention, and restricting high Na + accumulation in cytosol, this desirable adjustment also occurred due to saponin priming in this study (Figure ) depicted by high K + and low leaf Na + contents. The improved K + retention in leaf might be occurred due to activation of antioxidants such as phenols (Ismail et al., ). Ismail et al.…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al. () reported that exogenously applied rutin (a leaf phenol), improved K + retention accompanied by Na + pumping out of cell as indicated by strict control over voltage‐gated channels, thus maintaining proper water relations along with avoidance of Na + toxicity and appropriate K + /Na + ratio (Figure ). This K + /Na + ratio rather than alone Na + concentration has been widely considered as index of salinity tolerance (Houshmand, Arzani, Maibody, & Feizi, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] Among other non-enzymatic antioxidants, rutin levels were increased by over 25 fold in quinoa leaves under salinity stress. [46] In conditions. The rutin concentration increased more than three times.…”
Section: Determination Of Phenolic Acids and Rutin In H Thermophilummentioning
confidence: 98%